INFLUENCE OF NPK TABLET ON THE EARLY GROWTH OF SENGON (Paraserianthes falcataria L. Forberg) - Aris Sudomo (Jurnal Pemuliaan Tanaman Hutan, 2007)
The research is aimed to improve the productivity of sengon by testing the influence of NPK tablet as with four levels on growth. The research was conduced on November 2005 to August 2007 in the private forest in Sukamulih village. Sariwangi  Sub-District. The Design was Randomized Comlete Block Design (RCBD). The four treatments were no obtained from sengon,s growth on 21 months old minus its growth on 5 months old (fertilizing time). The result shows that faouir treatments of NPK tablets quantity to the sengon give insignificant influuence to the growth of sengon,s height and diameter in 21 months old 5 months old.